Search for third-generation scalar leptoquarks decaying to a top quark and a τ lepton at s = 13 Te - Sirunyan, A M; Tumasyan, A; Adam, W; Ambrogi, F; Asilar, E; Bergauer, T; Brandstetter, J; Brondolin, E; Dragicevic, M; Erö, J; Del Valle, A Escalante; Flechl, M; et al. (The European physical journal. C, Particles and fields, 2018)
A search for pair production of heavy scalar leptoquarks (LQs), each decaying into a top quark and a τ lepton, is presented. The search considers final states with an electron or a muon, one or two τ leptons that decayed to hadrons, and additional jets. The data were collected in 2016 in proton-proton collisions at s = 13 Te with the CMS detector at the LHC, and correspond to an integrated luminosity of 35.9 fb - 1 . No evidence for pair production of LQs is found. Assuming a branching fraction of unity for the decay LQ → t τ , upper limits on the production cross section are set as a function of LQ mass, excluding masses below 900 Ge at 95% confidence level. These results provide the most stringent limits to date on the production of scalar LQs that decay to a top quark and a τ lepton.